الصلح فى مجلس القضاء - العصيمي، فيصل بن سعد (وزارة العدل, 2014)
بين الباحث التالي: 1-أن الخصومة بين الناس تضطرهم للجوء للقضاء، والوقوف ببابه، وحضور مجلسه، فبحث المسائل المتعلقة بمشروعية الصلح في مجلس القضاء، ودراسة شروطه وآثاره، وصوره وأحواله. 2-عرف الباحث العنوان باعتباره مفرداً وتكلم عن الصلح من الناحية اللغوية والفقهية والقانونية. 3-عرف الباحث العنوان باعتباره مركبا واختار بأنه: عقد يحسم به-على وجه التراضي من الطرفين-نزاعا قائما أو يتوقي به نزاعا محتملا، وذلك بأن ينزل كل منهما على وجه التقابل عن جزء من ادعائه، ويتم إثباته، وتصديقه من القضاء". 4-الإشار إلى أركان الصلح، وأن الفقهاء عدو الصلح عقداً من العقود، واختلف الفقهاء في أركان الصلح فذهب الحنيفة إلى أن للصلح ركنا واحدا وهو: الصيغة التي ينعقد بها أما الجمهور فعد أركان الصلح ثلاثة: 1-الصيغة: وهي الإيجاب والقبول. 2-العاقدان: وهما المتصالحان. 3-محل العقد: وهو المصالح عنه والمصالح عليه. واختار الباحث رأي الجمهور وتحدث عنه بإيجاز. 5-الأصل أن الصلح في مجلس القضاء مندوب إليه غير أنه قد تجري الأحكام التكليفية الخمسة في بعض الأحوال. 6-ينبغي للقاضي أن يندب المتخاصمين إلى الصلح ويختمها عليه وهذا هو هدي النبي صلي الله علية وسلم في قضائه كإصلاحه صلي الله علية وسلم بين كعب ابن مالك وغر يمه. رواه البخاري. 7-ثمة حالا لا ينبغي للقاضي أن يرد فيها الخصوم إلى الصلح منها: 1-إذا تبين للقاضي وجه الحق. 2-إذا كانت المصلحة في الفصل بينهما قضاء كأن يخشي القاضي في عدم التزام الخصوم بالصلح أو الاختلاف في تنفيذه. 3-إذا تعذر الصلح. 4-إذا كان في الصلح جور أو ظلم على أحدهما. 8-تحدث الباحث عن حكم تأخير القاضي الحكم رجاء الصلح وأنه يجوز للقاضي في هذه الحالة تأخير الحكم للمصلحة المعتبرة مبينا فضائل الصلح في الدنيا والأخرة. 9-لمجلس القضاء شروطا يختص بها حال الصلح وهي: الشرط الأول: التراضي بين أطراف الخصومة على عقد الصلح وينبغي للقاضي أن يبتعد عن العوارض التي تقدح في هذا الشرط كالحياء والإكراه. الشرط الثاني: الأهلية والمقصود بها حرية التصرف. الشرط الثالث: التحقق من صيغة الصلح. الشرط الرابع: التحقق من محل الصلح واختلف الفقهاء في اشتراط المحل أي يكون معلوما على ثلاثة أقوال. الشرط الخامس: عدم مخالفة الصلح للشريعة الإسلامية. الشرط السادس: أن لا يغفل القاضي عن شروط مجلس القضاء. الشرط السابع: أن لا يدفع القاضي من ماله الخاص. الشرط الثامن: أن لا يكون الصلح متعلقا بحق الله تعالي. الشرط التاسع: أن يكون أطراف الدعوي ممن يملكون حق المصالحة ويدخل في هذا الشرط مسائل منهل: أ-صلح ولي القاصر. ب-صلح الوصي. ج-صلح ناظر الوقف. د-صلح الوكيل. ه-صلح الفضولي. 10-عقد الصلح عقد ملزم للطرفين انعقد، ولا يصح لأحدهما الرجوع عنه أو فسخه إلا بتراض من طرفيه فانعقاده في مجلس القضاء لازم ديانة وقضاء. 11-عقد الصلح كغيره من العقود في الفقه الإسلامي فقد يعتريه بعض الأمور تنقضه وتبطله. ومن أهم الأمور التي يبطل بها عقد الصلح: 1-افقالة. 2-عدم الوفاء. 3-الرد بخيار العيب أو الرؤية مالم يرضي صاحب الحق. 4-استهلاك ما وقع الصلح على منفعته. 5-موت أحد المتعقدين. 6-هلاك ما وقع الصلح على منفعته. 7-الاستحقاق والمراد به: استحقاق أحد الطرفين المتصالحين أحد العوضين. 8-إذا ظهرت البينة بعد انعقاد الصلح فقد اختار شيخ الإسلام ابن تيمية نقض الصلح. 9-إذا اصطلحا على دراهم بدنانير ثم افترقا قبل التقابض. 10-لو صالح عن عيب ثم زال العيب. 11-إذا كان الصلح على الانكار ثم أقر المنكر بعد الصلح. 12-لحاق المرتد بدار الحرب أو موته على الردة. The author tackles the following points: - Disputes among people force them to resort to the court and hearings. Therefore, it is necessary to discuss the issues related to legitimacy of reconciliation in the court session and study its conditions, effects and forms. - The definition of the vocabularies of the title of the study and linguistic, juristic and legal aspects of reconciliation. - The definition of the title as a collective one as “an agreement contract under which an existing dispute is settled and a potential one is prevented by reciprocating concessions by both disputing parties of parts of their claims which is documented and approved by the court.” - The pillars of reconciliation as jurists consider reconciliation as a contract but they differ as to the pillars of reconciliation: the Hanafites are of the opinion that reconciliation has one pillar, namely the format by which the contract is concluded while the majority of jurists are of the opinion that it has three pillars. These are: a) the format, b) the two contracting parties (the parties to the reconciliation) and the subject of the contract. The author chooses the opinion of the majority of jurists and discusses it briefly. - Originally, reconciliation in the court session is desirable but the five taklifee provisions may be applied in some cases. - The judge should encourage the disputing parties to reconcile as guided by the Prophet (peace and blessings be upon him). - There are some cases in which the judge may not request the disputing parties to resort to reconciliation. - If the judge is certain of the rightful party, - If it is better to settle the dispute by the court like fearing that the parties will not commit themselves to the reconciliation contract or differ on executing it, - If it is not possible to reach reconciliation, and - If reconciliation will result in causing injustice to either party. - The ruling on the judge’s delay of the judgment with the hope of reaching reconciliation stating the virtues of reconciliation in this life and the hereafter. - The court session needs to meet certain conditions in case reconciliation is sought. These are: - Agreement of the disputing parties to conclude the reconciliation contract. The judge should avoid any incidents that may violate this condition like shyness and duress. - Legal capacity which means free will. - Checking the reconciliation format. - Checking the subject of reconciliation, the knowledge of which is the subject of difference among scholars in three opinions. - The reconciliation should not violate the Islamic Sharee’ah. - The judge should not omit to observe the conditions of the court session. - The judge should not pay from his own money. - The subject of reconciliation should not relate to a right belonging to Allah. - The parties to the case should have the right to reconciliation. This condition includes some points including the following: - Reconciliation by the guardian of a minor, - Reconciliation by the administrator, - Reconciliation by a steward of an endowment, - Reconciliation by an attorney, and - Reconciliation by a busybody. - The reconciliation contract is binding to both parties; neither one may revoke or terminate it except with the consent of both parties. As soon as it is concluded in the court session, it becomes binding under religion and justice. - The reconciliation contract is like other contracts in the Islamic jurisprudence as it may be revoked and invalidated by some violations. The most important things that invalidate the reconciliation contract are: - Dismissal, - Failure of fulfillment, - Declination by defect option or sight unless the party having the right agrees to the same, - Consumption of the property the usufruct of which is the subject of reconciliation, - The death of either party, - Entitlement which means either party to the reconciliation is entitled to either compensation. - If the proof appears after concluding the reconciliation agreement, the reconciliation contract is terminated according to Ibn Taymiyah, - If the two parties agree to replace dirhams with dinars but they part with each other before receiving the same, - If the subject of the reconciliation is defective but such defect is removed, and - If the subject of reconciliation is denial but the denying party admits what he has denied after the reconciliation.
Keywords: الصلح -- القضاء -- الفقه الإسلامى